Improving Traceability and Collaboration in HDL Design with GitFlow and CI Pipelines - Farias, Renan Carlos Gomes de; Mendes, João Pedro Buzatti; Fontoura, Lisandra Manzoni; Rutzig, Mateus Beck (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
The complexity of digital hardware design has been increasing with the scale of CMOS technology. Thus, front-end design and verification teams face demands for modularity and traceability to shrink tape-out time and avoid failures on functional verification process. However, the employment of non-standard practices of project management in HDL-based workflows have long been spread in the microelectronics community. This work proposes a version control and continuous integration pipeline methodologies based on Gitflow aiming to improve collaboration between front-end and verification teams focusing on ASIC designs. By employing such an approach in a blueMacaw Microcontroller project, which resulted in a 22 nm tape-out, we achieved a highly effective workflow that ensured early error detection, traceability and strong team integration.